2016
DOI: 10.1111/hsc.12384
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in cardiovascular care in the English National Health Service (NHS): a scoping review of the literature

Abstract: There is a general understanding that socioeconomically disadvantaged people are also disadvantaged with respect to their access to NHS care. Insofar as considerable NHS funding has been targeted at deprived areas, it is important to better understand whether and why socioeconomic variations in access and utilisation exist. Exploring this question with reference to cardiovascular care, our aims were to synthesise and evaluate evidence relating to access to and/or use of English NHS services around (i) differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 128 publications
(252 reference statements)
0
5
0
Order By: Relevance
“…The scientific literature on healthcare utilization inequalities for elderly patients with CVD is sparse. Asthana et al performed a scoping review on inequity in cardiovascular care in the English National Health Service and found that females and older persons are consistently being associated with lower than expected rates of access to and use of cardiovascular care, South Asian populations having higher access while black populations lower access to care [43]. They found the geographical variation in access/use to be striking, and that barriers to access erected by healthcare professionals explain their results, rather than patients' failure to seek help in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature on healthcare utilization inequalities for elderly patients with CVD is sparse. Asthana et al performed a scoping review on inequity in cardiovascular care in the English National Health Service and found that females and older persons are consistently being associated with lower than expected rates of access to and use of cardiovascular care, South Asian populations having higher access while black populations lower access to care [43]. They found the geographical variation in access/use to be striking, and that barriers to access erected by healthcare professionals explain their results, rather than patients' failure to seek help in the first place.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, CVD mortality has been shown to be higher among those with better use of secondary prevention 36 ; different patterns in access and use of cardiovascular care by socioeconomic status and ethnicity has been found 53 as well as different specialized health service utilization. 54 Previous studies evidenced that major reductions in CVD mortality have been reached by controlling risk factors such as total cholesterol, blood pressure, smoking, and physical inactivity, and by contributing to the disease treatment, 55 although the importance of these contributions is still disputed.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…In the US, Black and Latinos are relatively under-represented in the primary healthcare system and less likely to be referred to cardiologists or cardiac surgeons. However, a review of cardiovascular care delivered in the National Health Service (NHS) in the UK has shown that Asians have higher levels of presentation and better access to secondary care management 22 but not necessarily primary care than other ethnic minority groups. 23 …”
Section: Discussionmentioning
confidence: 99%